The thermoluminescene responce of doped SiO optical fibres subjected to alpha particle irradiation - Ahmad Termizi Ramli, author; Badley David, author; Suhairul Hashim, author; Husin Wagiran, author; International Conference on Biomedical Application of High Enargy Ion Beams (2007 : United Kingdom)i (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL